Development of Siglec-9 Blocking Antibody to Enhance Anti-Tumor Immunity - Choi, Hyeree; Ho, Michelle; Adeniji, Opeyemi S.; Giron, Leila; Bordoloi, Devivasha; Kulkarni, Abhijeet J.; Puchalt, Alfredo Perales; Abdel-Mohsen, Mohamed; Muthumani, Kar (Frontiers in Oncology, 2021)
Sialic acid-binding Immunoglobulin-like lectin-9 (Siglec-9) is a glyco-immune negative checkpoint expressed on several immune cells. Siglec-9 exerts its inhibitory effects by binding to sialoglycan ligands expressed on cancer cells, enabling them to evade immunosurveillance. We developed a panel of human anti-Siglec-9 hybridoma clones by immunizing mice with Siglec-9-encoding DNA and Siglec-9 protein. The lead antibodies, with high specificity and functionality against Siglec-9, were identified through screening of clones. The in vitro cytotoxicity assays showed that our lead antibody enhances anti-tumor immune activity. Further, in vivo testing utilizing ovarian cancer humanized mouse model showed a drastic reduction in tumor volume. Together, we developed novel antibodies that augment anti-tumor immunity through interference with Siglec-9-mediated immunosuppression.